Consumption Behavior of Santri In The Perspective of Islamic Economics - Azhari, Mohammad Hasan; Masruroh, Nikmatul; Afif, Ahmad (Eastasouth Institute, 2025)
This study investigates the consumption behavior of santri (Islamic boarding school students) within the framework of Islamic economics at Miftahul Ulum Islamic Boarding School in Banyuputih Kidul, Lumajang. It aims to examine how students adopt the principles of halal (permissible), thayyib (wholesome), and moderation in their daily consumption practices. Using a descriptive qualitative approach, data were collected through interviews, observation, and documentation from selected students and school staff. The study reveals that most students display a basic awareness of Islamic consumption ethics, shaped by religious education and pesantren discipline. Nevertheless, their behavior is often challenged by modern consumption trends, peer influence, and financial constraints. The presence of a sharia-compliant cooperative within the pesantren supports efforts to align practice with Islamic economic values. The study concludes that while the foundation for ethical consumption is present, consistent reinforcement and practical support are necessary to bridge the gap between knowledge and behavior. These findings have implications for the integration of value-based consumption education in Islamic educational institutions.